Effects of Psychological Contract Breach on Organizational Citizenship Behaviour: Insights from the Group Value Model - Restubog, Simon Lloyd D.; Hornsey, Matthew J.; Bordia, Prashant; Esposo, Sarah R. (Journal of Management Studies, 2008)
abstractResearch on psychological contract breach has referenced social exchange as its dominant theoretical foundation. In this study, we draw insights from the group value model as a theoretical extension to explain employees' negative responses to psychological contract breach. According to the group value model, fair treatment by group members communicates symbolic messages about the relationship between the organization and the employee, and has implications for whether employees can take pride in their organizational membership. When people are treated unfairly, they lose trust in the organization and dis‐identify from the group. This in turn results in less willingness on the part of the employees to engage in organizational citizenship behaviours (OCBs). We tested these relationships across three studies. In Study 1, we conducted a longitudinal test of the role of trust as a mediator between breach and organizational identification. In Studies 2 (cross‐sectional) and 3 (longitudinal), we tested the complete model in which we examined the role of trust and identification in mediating the link between breach and OCBs. All three studies provided support for the mediated model. Furthermore, as predicted by the group value model, the hypothesized relationships emerged in response to relational but not transactional contract breaches. Theoretical and applied implications are discussed.